Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL) Berbantuan Alat Peraga Gaya Terhadap Pemahaman Konsep IPA Materi Gaya di SD Pangudi Utami - Yulius Tedy Wicaksana; Ela Suryani (Universitas PGRI Semarang, 2022)
The purpose of this study was to determine the effect of the contextual teaching and learning model assisted by force props on the understanding of the concept of force in fourth grade students of SD Pangudi Utami. This study uses a quantitative approach, experimental methods with Quasi Experimental Design, data collection techniques by conducting observations, concept understanding tests, and documentation, as well as for data analysis using SPSS for windows software. The results showed: 1) there was no significant difference in the average student concept understanding ability between the experimental class and the control class which could be seen from the sig value. (2-tailed) is 0.557 > 0.05, because the interest in learning for the two classes is the same, it can be seen from the results of the student activity observation sheet that is equal to 87.5%. 2) There is an effect of contextual teaching and learning model assisted by force props on students' conceptual understanding, seen from the significance value of 0.001 < 0.05, and the value of R2 = 0.601 = 60.1%. So it can be concluded that there is an influence between the contextual teaching and learning model assisted by force props on the understanding of the concept of force in fourth grade students of SD Pangudi Utami.